Self-healable functional polymer hydrogel electrolytes based energy storage devices for electronic applications / Maryam Hina - Maryam , Hina (2022)
The development of functional hydrogel electrolytes possessing superb ionic conductivity, self-healing, and mechanical properties simultaneously is still a challenge for application in energy storage devices. To overcome this issue, we developed novel poly (acrylamide) hydrogel through free radical mechanism and sodium montmorillonite clay was used as a physical crosslinker. Lithium trifluoromethanesulfonate (LiTF) salt, lithium trifluoromethanesulfonate/poly (3,4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT: PSS) (salt/conducting polymer), potassium hydroxide (KOH) base, and sulphuric acid (H2SO4) were added as ion sources in poly (acrylamide) hydrogels to prepare the hydrogel electrolytes. Numerous formulations of hydrogel electrolytes were developed by varying the amounts of salt, conducting polymer, base and acid to investigate the effect of ion sources on their properties and electrochemical characteristics. These poly (acrylamide) hydrogel electrolytes are poly (acrylamide)/ lithium trifluoromethanesulfonate (LiTF) (10 wt.%, 20 wt.%, 30 wt.%, and 40 wt.%≈AAM1, AAM2, AAM3, and AAM4), poly (acrylamide)/ lithium trifluoromethanesulfonate/ poly (3,4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT: PSS) (30 wt.% LiTF≈AAM3 and 40 mg, 60 mg, and 80 mg PEDOT:PSS≈PEDOTAAM32, PEDOTAAM33, and PEDOTAAM34), poly (acrylamide)/ potassium hydroxide (KOH) (5M and 6M KOH≈AAMKOH (5M) and AAMKOH (6M)), and poly (acrylamide)/ sulphuric acid (H2SO4) (1M and 2M≈ AAMH2SO4 (1M) and AAMH2SO4 (2M)) respectively. The synthesized hydrogel electrolytes were characterized using numerous techniques. The deconvolution of Fourier transform infrared spectroscopy (FTIR) spectra of hydrogel electrolytes was obtained to investigate the transport numbers and to observe the synergy between the presence of functional groups/molecules/ions and ionic conductivity. The ionic conductivity was measured at both ambient and higher temperatures (298K - 373K) for all the hydrogel electrolytes. The highest ionic conductivity (σ) was achieved by AAM3, PEDOTAAM34, AAMKOH (6M), and AAMH2SO4 (2M) (9.34, 13.70, 9.51, and 18.10 ×10-3 S/cm) at ambient temperature, respectively. The transference number measurements clarify the charge carriers' transport in the hydrogel electrolytes. Furthermore, the supercapacitor cells were fabricated by sandwiching the hydrogel electrolytes between symmetric carbon-coated graphite electrodes and electrochemical studies were performed. The highest performing cells, AC/AAM3/AC, AC/PEDOTAAM34/AC, AC/AAMKOH (6M)/AC, and AC/AAMH2SO4 (2M)/AC attained maximum specific capacitance of 143.00 F/g, 327.00 F/g, 240.00 F/g, and 387.75 F/g at 3 mV/s, respectively and the specific capacitance, energy density, power density in galvanic charge-discharge studies of these high performing symmetric supercapacitors were 155.47 F/g, 385.40 F/g, 213.85 F/g, and 405.81 F/g and an energy density of 21.48 W h/kg, 53.57 W h/kg, 29.49 W h/kg, and 56.18 W h/kg at power density of 99.78 W/kg, 100.008, 498.40 W/kg, and 499.40 W/kg, respectively, as demonstrated by cyclic voltammetry and galvanic charge-discharge studies. The real time supercapacitor devices developed by connecting the two symmetric cells in series were charged and then discharged by illuminating the light-emitting diode (LED). In addition, the self-healable characteristics of hydrogel electrolyte and symmetric supercapacitors were confirmed by powering up a light-emitting diode (LED) and cyclic voltammetry study. Moreover, the cyclic stability of the fabricated devices was conducted before and after self-healing for 5000 cycles. From the obtained results, it can be understood that all the hydrogel electrolytes and fabricated supercapacitors produced excellent results. This work ventures the frontiers of hydrogel electrolytes and flexible energy storage devices as a booming invention for smart electronic devices.